2021
DOI: 10.1021/acs.jpca.1c06772
|View full text |Cite
|
Sign up to set email alerts
|

On the Determination of Halogen Atom Reduction Potentials with Photoredox Catalysts

Abstract: The standard one-electron reduction potentials of halogen atoms, E°′(X•/–), and many other radical or unstable species, are not accessible through standard electrochemical methods. Here, we report the use of two Ir­(III) photoredox catalysts to initiate chloride, bromide, and iodide oxidation in organic solvents. The kinetic rate constants were critically analyzed through a derived diffusional model with Marcus theory to estimate E°′(X•/–) in propylene carbonate, acetonitrile, butyronitrile, and dichloromethan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 102 publications
4
31
0
Order By: Relevance
“…5). The spectral profile of the mono-reduced PS was in line with other reported spectra of related reduced iridium PS [49,[54][55][56][57]. The efficiency of charge separation after electron transfer (cage-escape yield) seems to be in the same range for the three PS, assuming similar molar absorption coefficient for the three mono-reduced PS.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…5). The spectral profile of the mono-reduced PS was in line with other reported spectra of related reduced iridium PS [49,[54][55][56][57]. The efficiency of charge separation after electron transfer (cage-escape yield) seems to be in the same range for the three PS, assuming similar molar absorption coefficient for the three mono-reduced PS.…”
Section: Resultssupporting
confidence: 87%
“…With [Ir(piq) 2 (bpy)] + and [Ir(piq) 2 (4,4′-(CH 3 ) 2bpy)] + , blue light excitation led to changes in absorbance that agreed with excited-state electron transfer from BIH to the excited photosensitizers and subsequent mono-reduced complex formation. Indeed, the double absorption peaks at 500 and 530 nm, coupled with the increased absorbance beyond 700 nm were in line with absorption changes observed in transient absorption spectroscopy with related photosensitizers [49,[54][55][56][57]. After 15 min of irradiation, an excess of potassium persulfate (K 2 S 2 O 8 ) was added as an irreversible electron acceptor to oxidize the monoreduced Ir photosensitizer and recover the ground-state Ir III products.…”
Section: Resultssupporting
confidence: 72%
“…Subsequent addition of excess TBACl to the NMR sample led to complete regeneration of the hydrogen signals corresponding to PTH (Figure S4). While this would ostensibly indicate reduction of PTH •+ by chloride, the one-electron potential for E °(Cl •/– ) in CH 3 CN has been crudely estimated as 1.46 V vs NHE; , therefore, reduction of PTH •+ by chloride is strongly thermodynamically disfavored.…”
Section: Resultsmentioning
confidence: 99%
“…Chlorine atoms have long been known as a powerful tool for C–H activation yet historically have seen little use in practical applications due to the harsh reaction conditions necessary to generate Cl • . Over the last decade, a number of groundbreaking studies have demonstrated facile chloride oxidation using photoredox catalysts, which have enabled new approaches to functionalize inert C–H bonds. Additionally, environmentally motivated applications rely on chloride oxidation as an important fundamental process for HCl splitting to store solar energy or for electric gradient generation for sea water desalination. However, the vast majority of these examples rely on noble metal photocatalysts to generate chlorine atoms because the one-electron reduction potential, (Cl • /– ), requires an incredibly potent photooxidant. Indeed, chloride ions are so redox inert that they are frequently used as counterions for common photocatalysts such as ruthenium polypyridyl compounds. , Synthesizing ruthenium or iridium coordination compounds that are strong photooxidants requires skillful ligand engineering , and such catalysts often suffer from stability issues. Moreover, photocatalysts based on noble metals are impractical at scale given the low natural abundance of these rare elements. Herein, we report a rare example of light-induced chloride oxidation catalyzed by an inexpensive, commercially available organic photocatalyst through unconventional one- and two-photon pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, kinetic measurements provide the sole method to infer thermodynamic information on redox couples such as E °′(Χ •/– ). 16 This submission reports a comparative method to quantify the increase in the formal reduction potential, E °′(Χ •/– ), imparted to the halide by sequestration relative to a freely diffusing halide ion.…”
Section: Introductionmentioning
confidence: 99%